Dampak Penggunaan Gadget Pada Siswa Kelas V SD Inpres Kinali - Hetty J. Tumurang; Richard D.H Pangkey; Fria Weime Sual (Peneliti.net, 2023)
This research was conducted based on the results of research carried out by researchers in class V of SD Inpres Kinali. This research aims to determine the positive and negative impacts of using gadgets on fifth grade students at SD Inpres Kinali. This type of research is qualitative research which takes place at SD Inpres Kinali. In qualitative research, the research instrument or tool is the researcher himself. The data collection technique in this research is that the data in this research was collected using observation guidelines, interview guidelines and documentation guidelines (Rukin, 2019: 1). In this research, researchers used the Miles and Huberman data analysis model which includes three stages, namely data reduction, data display, and drawing conclusions. This research obtained results namely that the positive impact of gadgets in terms of learning is good because they can be used as tools in the teaching and learning process. Meanwhile, the negative impact in terms of attitudes is the erosion of character in the teaching and learning process